Quantitative evaluation of pollen protein from Helianthus annuus for honey bee nutrition - Gupta, Amit (Innovare Journal of Life Sciences, 2017)
Objective- The objective of our study is to estimate the protein content from pollen (flowers) of Helianthus annuus and also determined in bee pollen (collected from honey bees). Methods: Nanodrop method is the most suitable method for protein estimation and also quantified the protein of pollen and bee pollen in KDa using SDS PAGE. In addition, proteins extracted from both the samples and exposed to hemolymph containing haemocytes pertaining to determine forward and side scatter using flow cytometry. Results: The data showed that pollen contained higher amount of protein content as compared to bee pollen. While SDS-PAGE analysis represents bands of various protein size from 14 KDa to 67 KDa (pollen, 25KDa and 34KDa; bee pollen, 25KDa). In an effort to determine the effect of proteins extracted from pollen and bee pollen directly exposed to haemolymph after feeding with these proteins diets and determined its shape and size (forward scatter) and granularity (side scatter) of the haemocytes. The data indicates that proteins from bee pollen showed enhancement in forward and side scatter as compared to pollen. Conclusion: Overall, the data suggests that bee pollen could be a potent candidate for nutrition to honey bees. Key words: Helianthus annuus, pollen; protein, haemocytes, haemolymph, flow cytometry.